Development of Worksheet Based on Scientific Approach to Improve Critical Thinking Skills - Ernawati, Tias; Sujatmika, Sigit (Gemilang Maju Publikasi Ilmiah (GMPI), 2021)
This study aimed to develop and determine the advisability of chemical worksheets based on a scientific approach to improve students' critical thinking skills. The research method uses five design research steps simplified from Borg's and Gall's research and development. The subject of this research are science education program students at one university in Indonesia. Validation subject matter feasibility on the worksheets is 4.34 (best criteria), while the feasibility is 4.17 (best standards). A random assessment from several students is obtaining an average score of 98.67% (positive response). The research results conclude that a worksheet is advisable for students. Expert opinion conveys that using a scientific approach to the problems presented in the worksheet reveals stimulates, encourages, and improves critical thinking skills.